2016
DOI: 10.17135/jdhs.2016.16.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Learning Experience of Dental Communication Course Training in Dental Hygiene Schools

Abstract: The purpose of this study was to develop a dental communication course in dental hygiene schools that included theory, practice, and skill for effective dental communication. Thirty-six senior dental hygiene students in a dental hygiene school took a dental communication course and responded to a questionnaire. The instrument used in the study was a modified form of Kim's communication skill self-assessment sheet. The self-assessment questionnaire about communication competencies was administered before and af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
(3 reference statements)
1
4
0
Order By: Relevance
“…The MI training program applied in this study is a program that reflects key theories based on basic MI principles, and was developed by collecting new strategies. The results of existing studies, recommending that communication and interview programs should be coupled with theory lectures and practice for effectiveness 5,17,[19][20][21] , support the strategy of this study. As such, this study has provided a number of cases as an indirect practice, and included methods of To evaluate the effectiveness of the MI training program, 43 study participants were recruited.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…The MI training program applied in this study is a program that reflects key theories based on basic MI principles, and was developed by collecting new strategies. The results of existing studies, recommending that communication and interview programs should be coupled with theory lectures and practice for effectiveness 5,17,[19][20][21] , support the strategy of this study. As such, this study has provided a number of cases as an indirect practice, and included methods of To evaluate the effectiveness of the MI training program, 43 study participants were recruited.…”
Section: Discussionsupporting
confidence: 52%
“…DeBate et al 23) confirmed the improvements in knowledge, techniques, and self-efficacy through a MI training workshop for college students in dentistry and dental hygiene; Choi et al 5) reported that college students Moreover, this study has utilized measurement tools that involve the self-evaluation by participants and analysis by the researcher. This may be influenced by subjective opinions.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…To change the condition, high-level dental management program should be provided by learning comprehensive clinical dental activities as well as the education on dental hygiene. The important role of a dental hygienist is to enhance the dental health, meet the requirements, and continue to manage for evaluating, maintaining, and improving the dental hygiene process by confirming the dental health problems of a subject and conduct a designed planned as well as inducing behavioral changed through granting intrinsic motivator [9].…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, to increase communication competency of dental hygiene students it needs efforts to improve self-efficacy and satisfied interpersonal relationship as well as communication skill education. Impact Factor: 1.745 (I2OR)Http://www.ijetmr.com©International Journal of Engineering Technologies and Management Research [1][2][3][4][5][6][7][8][9][10][11][12] College students are at the developmental stage that requires adaptation to a diversity of changes in the psycho-social environment and are in the critical period that requires them to experience close and positive interpersonal relationships with various people around them and establish subjectivity 3 . One of the common capabilities that those studies on the key capabilities for college students suggest is communication competency 4 .…”
mentioning
confidence: 99%